Use of Accelerometers to Examine Sedentary Time on an Acute Stroke Unit. Issue 3 (July 2015) - Mattlage, Anna E.; Redlin, Sara A.; Rippee, Michael A.; Abraham, Michael G.; Rymer, Marilyn M.; Billinger, Sandra A.
Abstract : Background and Purpose: Observational studies demonstrate low levels of physical activity during inpatient stroke rehabilitation. There are no prior studies that have objectively measured sedentary time on the acute stroke unit and whether sedentary time is related to functional outcomes. The purpose of this study was to characterize sedentary time after acute stroke and determine whether there is a relationship to functional performance at discharge. Methods: Thirty-two individuals (18 men; 56.5 ± 12.7 years) with acute stroke were enrolled within 48 hours of hospital admission. An accelerometer was placed on the stroke-affected ankle to measure 24-hour activity and was worn for 4 days or until discharge from the hospital. Performance of activities of daily living, walking endurance, and functional mobility were assessed using the Physical Performance Test, Six-Minute Walk Test, and Timed Up and Go, respectively. Results: Mean percent time spent sedentary was 93.9 ± 4.1% and percent time in light activity was 5.1 ± 2.4%. When controlling for baseline performance, the mean time spent sedentary per day was significantly related to Physical Performance Test performance at discharge ( r = −0.37; P = .05), but not the Six-Minute Walk Test or Timed Up and Go. Discussion and Conclusions: Patients with acute stroke were sedentary most of their hospital stay. To minimize the potential negative effects of inactivity, our data suggest that there should be greater emphasis on increasing physical activity during the hospital stay. Video Abstract Available for more insights from the authors (Supplemental Digital Content 1, http://links.lww.com/JNPT/A101 ). Abstract : Supplemental Digital Content is Available in the Text.